2022
DOI: 10.1055/a-1964-8181
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Complications of Biologic and Synthetic Mesh in Breast Reconstruction: A Systematic Review and Network Meta-Analysis

Abstract: Background:In breast reconstruction, synthetic meshes are frequently used to replace acellular dermal matrix (ADM), since ADM is expensive and often leads to complications.However, there is limited evidence that compares the types of substitutes. This study aimed to compare complications between materials via a network meta-analysis. Methods:We systematically reviewed studies reporting any type of complication from 2010 to 2021. The primary outcomes were the proportion of infection, seroma, major complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As a result, the use of a mesh has dramatically fallen. In fact, a recent meta-analysis of 17 studies, evaluated complication rates comparing the acellular dermal matrix (ADM), a synthetic absorbable mesh, a synthetic non-absorbable mesh and no matrix [ 75 ]. The infection rate was higher for ADM, the seroma rate was lower for the synthetic absorbable matrix (OR: 0.2) and the synthetic non-absorbable matrix (OR: 0.1 compared to ADM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the use of a mesh has dramatically fallen. In fact, a recent meta-analysis of 17 studies, evaluated complication rates comparing the acellular dermal matrix (ADM), a synthetic absorbable mesh, a synthetic non-absorbable mesh and no matrix [ 75 ]. The infection rate was higher for ADM, the seroma rate was lower for the synthetic absorbable matrix (OR: 0.2) and the synthetic non-absorbable matrix (OR: 0.1 compared to ADM).…”
Section: Discussionmentioning
confidence: 99%
“…The infection rate was higher for ADM, the seroma rate was lower for the synthetic absorbable matrix (OR: 0.2) and the synthetic non-absorbable matrix (OR: 0.1 compared to ADM). However, clinically significant complications (grade 2 and 3) did not differ between patients who received prepectoral or subpectoral implants [ 75 ]. In the above meta-analysis, major complications were similar whether or not a mesh was used.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a higher infection rate with the use of ADM compared to synthetic mesh or no mesh after MIBR. A recent systematic review found a 2.97 times higher infection rate with ADM compared to no mesh but no significant difference between synthetic meshes and no mesh use in infection rate [ 9 ]. In another literature review by Ellis et al, infection rates with ADM in the literature ranged between 0.2% and 35.8%, while with synthetic mesh use in breast reconstruction, studies report an infection rate between 1.3% and 6.1% [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…While ADMs are widely used, there is no strong evidence for their superior outcomes compared to synthetic meshes. A recent systematic review found lower infection and seroma rates in synthetic meshes compared to ADMs but no significant difference in re-operation rates and implant removal [ 9 ]. However, there is no strong evidence comparing patient-reported outcomes (PROMs) between synthetic meshes and biologic matrices.…”
Section: Introductionmentioning
confidence: 99%
“…ADMs have a significant economic burden and can be a deterrent to use while the relative cost-effectiveness of synthetic meshes makes it an appealing alternative option [48]. Meshes are also associated with less frequent infections and seroma formation in comparison with ADMs [49]. It is important to understand that though offering similar support, synthetic meshes do not provide additional soft tissue coverage, which ADMs can provide, and caution should be exercised with thin mastectomy skin flaps.…”
Section: Acellular Dermal Matrices and Synthetic Meshmentioning
confidence: 99%